Castilian speakers’ attitudes towards accents and regional stereotypes in Spain - Gallego, Juan Carlos; Rodríguez, Anthony (Sociolinguistic Studies, 2013)
This study investigated what Castilian speakers thought about their own and ten other regional varieties of Spanish in Spain, including their perception of regional stereotypes. A questionnaire containing statements about language attitudes and regional stereotypes was administered to 620 subjects. Results were compared across language varieties, and by age, gender and level of formal education. Comparisons were also made between Castilian speakers from Madrid and the rest of the group. Findings reveal that Castilians like their own variety of Spanish better than almost any other, but that they also show a positive attitude toward the other ten varieties. Age proved to be a significant variable, in particular with regard to Catalan Spanish, with the oldest and the youngest groups showing a slight dislike of that variety. Age, gender and level of education also made a difference when analyzing responses to stereotypes. No important distinctions were found between the Madrileno and Castilian subgroups. Through this study, we are better able to understand how speakers of a standard dialect perceive non-standard dialects of that language, and how their attitudes may change over time.